2023
DOI: 10.3233/jpd-225053
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Loop Adaptive Deep Brain Stimulation in Parkinson’s Disease: Procedures to Achieve It and Future Perspectives

Abstract: Parkinson’s disease (PD) is a neurodegenerative disease with a heavy burden on patients, families, and society. Deep brain stimulation (DBS) can improve the symptoms of PD patients for whom medication is insufficient. However, current open-loop uninterrupted conventional DBS (cDBS) has inherent limitations, such as adverse effects, rapid battery consumption, and a need for frequent parameter adjustment. To overcome these shortcomings, adaptive DBS (aDBS) was proposed to provide responsive optimized stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 169 publications
(388 reference statements)
0
2
0
Order By: Relevance
“…To overcome these shortcomings, novel adaptive DBS (aDBS), an emerging field, recognizes input signals associated with changes in patient symptoms, such as brain or motor signals, to provide responsive, optimized stimulation in real-time ( Guidetti et al, 2021 ). Its benefits have been demonstrated in several animal experiments ( Johnson et al, 2016 ) and clinical studies ( Little et al, 2016 ), potentially surpassing those of conventional cDBS as a therapeutic option for non-motor symptoms in PD ( Wang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these shortcomings, novel adaptive DBS (aDBS), an emerging field, recognizes input signals associated with changes in patient symptoms, such as brain or motor signals, to provide responsive, optimized stimulation in real-time ( Guidetti et al, 2021 ). Its benefits have been demonstrated in several animal experiments ( Johnson et al, 2016 ) and clinical studies ( Little et al, 2016 ), potentially surpassing those of conventional cDBS as a therapeutic option for non-motor symptoms in PD ( Wang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In theory, adaptive DBS works by responding to input brain signals by providing optimized stimulation parameters to improve the therapeutic efficacy and increase battery longevity. A recent review paper now provided a comprehensive summary of advances for adaptive DBS ( Wang et al, 2023 ), where the researchers suggested that EPs may be a promising source of input signals for adaptive DBS. Obviously, their effectiveness and applicability still need to be confirmed in a large-scale study.…”
Section: Discussionmentioning
confidence: 99%